Accumulation through derealization: How corporate violence remains unchecked. (October 2016) - Varman, Rohit; Al-Amoudi, Ismael
This study examines the alleged organization of violence by Coca-Cola through a field study conducted in a village in India. It draws on the works of Judith Butler to show how subaltern groups are derealized and made into ungrievable lives through specific, yet recurrent, practices that keep violence unchecked. Many participants attempt to resist derealization through protest activities that showcase their vulnerability. However, the firm appropriates their claims to vulnerability through a paternalistic discourse that justifies intensified violence and derealization. This research offers insights into accumulation through derealization and on the effects of resistance to it.